1987
DOI: 10.1902/jop.1987.58.2.86
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Hand Scaling and Ultrasonic Debridement in Furcations as Evaluated by Differential Dark‐Field Microscopy

Abstract: There have been no previous reports in the literature comparing the effects of hand scaling with ultrasonic debridement in furcations, or which have used dark-field microscopy for this comparison. The purpose of this study was to compare the efficacy of these two modes of debridement in various classes of furcations, using gingival crevicular fluid flow and dark-field microscopy as parameters. A total of 33 furcated molars were evaluated. Results indicated that both hand scaling and ultrasonic debridement were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 17 publications
4
48
0
1
Order By: Relevance
“…The dental calculus and cement contaminated can be removed by manual or ultrasonic debridement, and the studies show similar effectiveness in both approaches. [9][10] In a clinical evaluation for six months to evaluate manual and ultrasonic debridement the results were similar.…”
Section: Introductionmentioning
confidence: 81%
“…The dental calculus and cement contaminated can be removed by manual or ultrasonic debridement, and the studies show similar effectiveness in both approaches. [9][10] In a clinical evaluation for six months to evaluate manual and ultrasonic debridement the results were similar.…”
Section: Introductionmentioning
confidence: 81%
“…Working with the microscope has shown that untreated pockets of chronic periodontitis with a depth of more than 3 mm are always associated with hard deposits 2326…”
Section: Discussionmentioning
confidence: 99%
“…Extracted teeth scalers shape the root rather than clean it 24. Ultrasonic scalers do less harm to the root surfaces, but perfect cleaning is not possible, as they glide over crevices 2426…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasonic instruments was propagated due to the reduction of clinical time and greater ease of access to deep pockets and furcation areas, according to Leon and Vogel, 1987 [5] Ribeiro et al, 2004 [6] who conducted a systematic review of the literature on manual and ultrasonic instrumentation and describe among others the following studies: Oosterwaal et al,1987 [7] compared the instrumentations, manual and ultrasonic in bags of 6 to 9 mm, and found that both were equally effective in decreasing the number of colony units; Boretti et al,1995 [8], stated that the use of instrumentation showed a reduction in time with the use of ultrasonic devices around 49%. Hunter et al, 1984 [3]; Garnick and Dent, 1989 [9] said that even studies demonstrating the effectiveness of both instrumentations in the removal of biofilm and calculus instrumentation performed with ultrasound device allows better access to deep pockets and furcation areas; Dragoo, 1992 [10] evaluated the effectiveness of instrumentation when using conventional ultrasonic horns and curettes, and concluded that the ultrasonic tip modified to be thinner than the conventional and that the curette, he could get closer to function purse background effectiveness of scraping on all sides of the tooth when compared to conventional and hand tools.…”
Section: Introductionmentioning
confidence: 99%